Strain monitoring for shallow foundation using the application of Brillouin Optical Time Domain Analysis sensing system (BOTDA). Issue 1 (September 2020) - Sirat, Qurratu Aini; Awang Ismail, Dayangku Salma; Ahmad, Izwan Shah; Kassim, Azman
Abstract: Stability analysis of the foundation is closely associated with soil deformations and since the stability of the foundation affect the stability of the entire structure, instrumentation and monitoring play an important role in monitoring its performances. The usage of Brillouin Optical Time Domain Analysis (BOTDA) sensing system is implemented in this study to monitor the soil deformation, yet the accuracy of the fiber sensing technology is still a concerned point. Thus, the aims of the paper are to evaluate the parameter configuration of the BOTDA interrogator and to analyze the fiber optic-soil interaction from the strain distribution data under the influence of incremental surcharge loading. The methodology presented are experimental works for calibration of fiber optic as for acquiring the coefficients by calibrating the signal difference in terms of strain and thermal characteristics. Then, the coefficients use used in a small-scale physical model to observe the fiber optic-soil interaction under the influence of surcharge loading. From the result of this study, the coefficient over a Brillouin signal for Fujikura optical fiber is 20 µε and 1°C for strain and temperature respectively. The fiber-soil interface also increases with the implementation of anchorage system. In conclusion, optical fiber sensing is a good approach for instrumentations and monitoring for geotechnical structures as fiber optics is sensitive to the movement of the soil.